2018
DOI: 10.3390/nu10020152
|View full text |Cite
|
Sign up to set email alerts
|

Database Analysis of Depression and Anxiety in a Community Sample—Response to a Micronutrient Intervention

Abstract: Background: Depression and anxiety are common mental health concerns worldwide. Broad-spectrum multi-vitamin/mineral approaches have been found to alleviate a number of psychiatric symptoms. We investigated the effects of a nutrient intervention program, which includes optimizing vitamin D levels, on depression and anxiety outcomes from community-based program. Methods: We evaluated self-reported health measures of depression and anxiety collected as part of a community-based program focused on optimizing over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 59 publications
0
33
0
1
Order By: Relevance
“…Our study revealed significant associations of lower 25(OH) D3, Ca 2+ , phosphorus, and Alb levels and self-reported problems with depression or anxiety. Nutrition and dietary habits have been related to the occurrence of depression or anxiety [29,30,31]. Several authors have found that vitamin D deficiency was highly prevalent among depressed or anxious patients, and supplementation had a significant influence on mental health improvements, particularly for depression [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study revealed significant associations of lower 25(OH) D3, Ca 2+ , phosphorus, and Alb levels and self-reported problems with depression or anxiety. Nutrition and dietary habits have been related to the occurrence of depression or anxiety [29,30,31]. Several authors have found that vitamin D deficiency was highly prevalent among depressed or anxious patients, and supplementation had a significant influence on mental health improvements, particularly for depression [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological surveys show that approximately 8% and 3% of adults over 65 years of age still meet formal diagnostic criteria for depression or anxiety disorders, respectively [31,32,33]. This is significant given that the number of adults over 65 years is projected to increase in the coming decades and given these conditions compound the effects of physical comorbidities [36,37,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to determine whether change in individual nutrient levels could predict strength of response to a nutrient intervention. Others have proposed that change in serum nutrient levels is an important component associated with outcome (Hambly et al, 2017; Kimball, Mirhosseini, & Rucklidge, 2018); however, what has never been investigated is whether the change as measured in peripheral blood is necessary for treatment benefit to occur.…”
Section: Discussionmentioning
confidence: 99%
“…The chosen variant of quoting the answers is most widely used in the US [ 25 ]. For the self-perceived level of anxiety, we used a short scale, with 5 levels, frequently used in the field [ 26 ].…”
Section: Methodsmentioning
confidence: 99%